2022
DOI: 10.1007/s40519-022-01385-8
|View full text |Cite
|
Sign up to set email alerts
|

Weight stigma in patients with overweight and obesity: validation of the Italian Weight Self-Stigma Questionnaire (WSSQ)

Abstract: Purpose This study aimed to explore the factorial structure of the Italian Weight Self-Stigma Questionnaire (WSSQ) (Study1); and to test structural validity, internal consistency, test–retest reliability, and measurement invariance of the questionnaire across gender, Body Mass Index (BMI), age and occurrence of previous hospitalization for obesity (Study2). Methods At admission into a hospital-based program for weight reduction and rehabilitation, 150 inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
(147 reference statements)
1
9
0
Order By: Relevance
“…Similar to previous findings, the Thai WSSQ showed measurement invariance across gender (female vs. male) and weight status (non-overweight vs. overweight) [ 2 , 25 ]. The results illustrated that the factor structure of the WSSQ is similar across both the gender (female and male) and weight status (non-overweight and overweight) subgroups.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to previous findings, the Thai WSSQ showed measurement invariance across gender (female vs. male) and weight status (non-overweight vs. overweight) [ 2 , 25 ]. The results illustrated that the factor structure of the WSSQ is similar across both the gender (female and male) and weight status (non-overweight and overweight) subgroups.…”
Section: Discussionsupporting
confidence: 84%
“…The WSSQ is a self-reported instrument assessing weight-related self-stigma [ 25 ]. It contains 12 items, and every item is rated on a 5-Likert point scale (1 = strongly disagree to 5 = strongly agree ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from this background, in line with previous researches (Panzeri et al, 2021c;Parola et al, 2022;Rossi et al, 2022), the aim of the first study here reported was to extensively examine the factorial structure of the PDI. To achieve this goal, EGA was used: an innovative technique, particularly precise and sensitive in identifying the correct number of factors/dimensions (Golino and Epskamp, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…The Weight Self-Stigma Questionnaire (WSSQ) is an instrument specifically designed to measure weight self-stigma in populations with overweight or obesity that was originally developed in the United States [ 13 ]. The WSSQ has been validated so far in German [ 14 ], Chinese [ 15 ], Turkish [ 16 ], French [ 17 ], Italian [ 18 ], and Malaysian [ 19 ] populations. The original version of the WSSQ [ 13 ] showed a two-factor model, corresponding to self-devaluation (negative thoughts and emotions about being obese) and fear of enacted stigma (involves the perception of being discriminated, as well as the identification to a stigmatized group), and it had adequate reliability (with Cronbach’s alphas = 0.81 and 0.87, respectively).…”
Section: Introductionmentioning
confidence: 99%